Experimental analysis of a hybrid liquid desiccant system with nonadiabatic air-solution contactors at different working conditions. - Prieto, Juan; Ortiga, Jordi; Peña, Xabier; Alonso, Laura; Gommed, Khaled; Grossman, Gershon; Coronas, Alberto (My University, 2016)
The performance of a hybrid liquid desiccant prototype with non-adiabatic air-solution contactors is analyzed in this paper. In order to avoid corrosion all the components that are in direct contact with the liquid desiccant are made of plastic, especially the air-solution contactors that are made of polypropylene. The hybrid liquid desiccant system (HLDS) is an air-conditioner that separately controls the humidity and temperature of two locker rooms of a swimming-pool in Taipei (Taiwan). The experimental prototype is firstly presented. In addition, the experimental performance of the HLDS during its operation in Taipei is shown and discussed. The thermal capacity of the system working at full load is included as well as the supplied air conditions reached by the system at different ambient air conditions. The presented HLDS shows an adequate control of the humidity and temperature of the locker rooms at different operational conditions. At the same time, corrosion which is one of the main problems in liquid desiccant systems has been eliminated because of the use of plastic materials.
Acceso abierto: https://explore.openaire.eu/search/publication?articleId=od______1266::dec4186d8898deb3ec960842da43bb12
Keywords: Aire acondicionado; Dehumidification; Liquid desiccant; Air-Conditioning